The Influence of Leadership, Motivation, Environment and Discipline on Work Performance of the North Bengkulu Argamakmur Environmental Service - Muhamad Galy Njoman Ari Pribowo; Antonius Antonius (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research is motivated by the importance of improving employee performance in order to produce quality employees. The respondents of this research are all employees of Dinas Lingkungan Hidup Argamakmur Bengkulu Utara with the total number 64 people, with the sampling method is total sampling. Data analysis techniques using multiple linear regression analysis and hypothesis testing. The results of this study indicate that the variables of work motivation, work environment and work discipline partially or individually influence employee performance with a probability value (sig) of each variable. Leadership (X1) with a probability value (sig) 0.013 <alpha 0.05 has a significant effect on work performance. Work motivation (X2) with a probability value (sig) of 0.000 < alpha 0.05 has a significant effect on work performance. Work environment (X3) with a probability value (sig) 0.042 <alpha 0.05 has a significant effect on work performance. And work discipline (X4) with a probability value (sig) 0.001 <alpha 0.05 has a significant effect on work performance.